Partisipasi Politik Masyarakat dalam Proses Pembentukan Peraturan Desa di Desa Beran Kecamatan Kepil Kabupaten Wonosobo Tahun 2021 - Alfiyani, Rita; Prihatmoko, Joko Juli (JURNAL LANSKAP POLITIK, 2023)
This study aims to describe community political participation, as well as identify what factors influence the level of community political participation in the process of forming village regulations in Beran Village in 2021. This research uses a descriptive qualitative method. Data collection techniques were taken through in-depth interviews with relevant informants, field observations, and literature studies. It is intended that the data obtained is more relevant and facilitates the grouping of data. The results of the study show that the political participation of the people of Beran Village in the process of forming the 2021 village regulations is still relatively low, seen from the level of attendance and aspirations of the community during village meetings and village meetings. factors that affect the level of political participation of the people, namely internal factors (age, education level, type of work, and income), and external factors (government leadership and outreach).